The Efforts to Increase Teachers' Competence in Establishing KKM Through Training Activities MTS Daarul Muhsinin Janji Manahan Kawat Kabupaten Labuhanbatu - Hasan Basri (research, training and philanthropy institution Natural Aceh, 2021)
KKM is the target of the education unit in achieving the competence of each subject. The education unit must make every effort to exceed the specified KKM. The success of achieving KKM is one of the benchmarks for the performance of the education unit in implementing educational programs. Education units with a high KKM and implemented responsibly can be a benchmark for the quality of education for the community. Therefore, there needs to be activities that can improve teacher competence in compiling KKM so that KKM in schools can really be measured and accounted. The method in this research is the action research method (action research). This study uses a qualitative approach. The subject of the study was the teacher of MTs Daarul Muhsinin in the area of ​​the Ministry of Religion Office of Labuhan Batu Regency. The number of teachers who participated in this activity was 29 people. The results of the first cycle activities still cannot be said to be successful, this is because the average score of the teachers is still below 50 or less. In the second cycle, the training activities were followed up by providing practical assistance, in which the researcher and participants jointly set the minimum completeness criteria. In the second cycle, the results of determining the minimum completeness criteria for subjects prepared by the teacher increased sharply, this was evidenced by the teachers getting an average score of 85 or good. From the results of the study it can be concluded that there is an increase in teacher competence in determining minimum completeness criteria. In the first cycle the average teacher competency score was 25 or less, then increased to 85 or good. This means that training activities have a positive impact on increasing teacher competence in determining minimum completeness criteria.